Use of Massive Open Online Courses (MOOC) by Teachers of Ukrainian Universities: Survey Results - Sharov, Sergii; Biliatska, Valentyna; Kolmakova, Vira; Chernova, Ganna; Miroshnichenko, Mykola; Шаров, Сергій Володимирович; Мірошніченко, Микола Юрійович (Frankfurt am Main : Published under CC-BY, 2025)
EN: The research analyzes the results of a survey of university teachers on the use of massive open online courses (MOOC) in the educational process and for personal self-development. 2,824 respondents from 155 universities located throughout Ukraine took part in the survey. The authors’ questionnaire was created with Google Forms. The analysis of responses has revealed that 88.8% of respondents use MOOC. The most famous Ukrainian online platform among teachers is Prometheus (54.7% of respondents). The most famous foreign platform is Coursera (31.2% of teachers). In addition to quantitative analysis of simple responses, we used a hierarchical clustering method to analyze extended responses, and we made a list of 82 standardized responses (SR). It was found that the use of MOOC had increased the amount of teachers’ knowledge and their practical experience. The most important advan tages of using MOOC in the educational process are additional learning material, experience in non-formal education, etc. As for weaknesses, these are low-quality connection, low quality of some online courses, lack of motivation among teachers. The obtained results expanded the list of advantages and disadvantages of MOOC, and the formed list of SR can become the basis for further research where we plan to study the ways of increasing teacher motivation to use MOOC in the educational process.
Keywords: online learning; massive open online courses (MOOC); online course; higher education; teachers; MOOC; онлайн-курс; вчителі; освітній процес; старша школа